High Volume-Per-Dose and Low Resistivity of Cobalt Nanowires Grown by Ga(+) Focused Ion Beam Induced Deposition - Sanz-Martín, Carlos (Nanomaterials (Basel), 2019)
The growth of ferromagnetic nanostructures by means of focused-Ga(+)-beam-induced deposition (Ga(+)-FIBID) using the Co(2)(CO)(8) precursor has been systematically investigated. The work aimed to obtain growth conditions allowing for the simultaneous occurrence of high growth speed, good lateral resolution, low electrical resistivity, and ferromagnetic behavior. As a first result, it has been found that the competition between deposition and milling that is produced by the Ga(+) beam is a limiting factor. In our working conditions, with the maximum available precursor flux, the maximum deposit thickness has been found to be 65 nm. The obtained volumetric growth rate is at least 50 times higher than in the case of deposition by focused-electron-beam-induced deposition. The lateral resolution of the deposits can be as good as 50 nm while using Ga(+)-beam currents lower than 10 pA. The high metallic content of the as-grown deposits gives rise to a low electrical resistivity, within the range 20–40 µΩ·cm. Magnetic measurements confirm the ferromagnetic nature of the deposits at room temperature. In conclusion, the set of obtained results indicates that the growth of functional ferromagnetic nanostructures by Ga(+)-FIBID while using the Co(2)(CO)(8) precursor is a viable and competitive technique when compared to related nanofabrication techniques.